THE EFFECTIVENESS OF MARKETING STYLE BY SPA THERAPIST IN BOOSTING SALES TO AND LOCAL TOURISTS IN KUTA - Komang Shanty Muni Parwati (Institut Pariwisata dan Bisnis Internasional, 2016)
Spa industry flourishes and influences the development of hospitality industry in Bali. Various spa facilities in Bali accommodate varied Spa service demands that inspired by local and abroad culture that offers comfort, relaxation, and stress-free with traditional touch of massage technique that of which the purpose of people who want to enjoy the spa in Bali. The presence of domestic and local tourists should be utilized to support local Spa industries. This study aimed to describe the effectiveness of the marketing style by the therapist in order to increase the domestic and local tourists for visiting the local’s SPA and therapist’s attitude in offering the local products and the local treatments to attract the consumers. This study is using descriptive-quantitative approach. The study conducted in Kuta tourism area with spa therapist’s daily activities, how they are offering their product and giving the service to the domestic and local tourists as the subject in accordance to the stages of the study. The instrument that used in this study is the sheets of promotion effectiveness, sheets of therapist marketing style and sheets of attitude, by using scales that is adjusted in the study. The result of this study shows that, 1) effectiveness of promotion that is done with an appropriate marketing style can boost costumers, 2) formal Indonesian language that is used correctly can make domestic and local tourists more interested in taking treatments. Based on the findings it is concluded that the promotion is effective if the marketing style of the therapist improved and used intensively to boost sales and costumer visit in the spa. The suggestions that can be given based on this study are that improving and developing the marketing style and ability of the therapist to communicate directly to domestic and local tourists may boost sales. Spa industry stakeholders and language teachers should be involved to support local spa industry.Spa industry flourishes and influences the development of hospitality industry in Bali. Various spa facilities in Bali accommodate varied Spa service demands that inspired by local and abroad culture that offers comfort, relaxation, and stress-free with traditional touch of massage technique that of which the purpose of people who want to enjoy the spa in Bali. The presence of domestic and local tourists should be utilized to support local Spa industries. This study aimed to describe the effectiveness of the marketing style by the therapist in order to increase the domestic and local tourists for visiting the local’s SPA and therapist’s attitude in offering the local products and the local treatments to attract the consumers. This study is using descriptive-quantitative approach. The study conducted in Kuta tourism area with spa therapist’s daily activities, how they are offering their product and giving the service to the domestic and local tourists as the subject in accordance to the stages of the study. The instrument that used in this study is the sheets of promotion effectiveness, sheets of therapist marketing style and sheets of attitude, by using scales that is adjusted in the study. The result of this study shows that, 1) effectiveness of promotion that is done with an appropriate marketing style can boost costumers, 2) formal Indonesian language that is used correctly can make domestic and local tourists more interested in taking treatments. Based on the findings it is concluded that the promotion is effective if the marketing style of the therapist improved and used intensively to boost sales and costumer visit in the spa. The suggestions that can be given based on this study are that improving and developing the marketing style and ability of the therapist to communicate directly to domestic and local tourists may boost sales. Spa industry stakeholders and language teachers should be involved to support local spa industry.